KOMPETENSI INTI KARYAWAN PENGELOLA EVENT MEETING DI HOTEL GUMILANG REGENCY HOTEL - Budi Setiawan; Nuraeni Ningrum (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
This research aims to obtain in-depth information about the core competencies within the company include core competencies possessed by the human resources to manage meeting activity at a star hotel. Based on its activities, the core competencies here includes several main dimensions namely interpersonal skills, personal skills and business skills, which are then described in sub dimensions. In this study, the descriptive method is used to present a picture of the phenomenon actually occurs in the hotel at that time. The results show that in the event meeting handling had actually requires human resources with core competencies such as mastering computer (63.64%), team work ability (96.97%), having a knowledge management (70.45), knowing self-management (100 %), and mastering the attitudes of leadership (97.73%). In general, the condition occurs is reliable. However, it has not reached its optimal ability thus could be the constraint to become an organization with excellence and uniqueness sustainability.